Exploring Taxation Dynamics: Perceptions and Strategies in Marketing Practices - Kurniawan, Gogi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study investigates taxation dynamics within marketing practices, aiming to explore consumer perceptions, firm strategies, and their implications for profitability and market performance. Employing a qualitative analysis of existing literature, the research examines key themes and patterns in taxation-related studies. The study finds that consumer perceptions significantly influence purchasing decisions, with tax perception impacting willingness to pay and brand preferences. Firms employ various strategies such as tax planning, pricing adjustments, and lobbying efforts to navigate taxation dynamics and optimize financial outcomes. Tax planning emerges as crucial for minimizing tax liabilities and enhancing competitiveness. Additionally, firms adjust pricing strategies and product portfolios in response to tax policies, while tax-efficient supply chain management mitigates tax-related risks. The interaction between taxation dynamics and market performance has significant implications for firm profitability, market structure, and economic growth. Higher tax burdens correlate with reduced corporate earnings and investment, influencing market competition and innovation. The effectiveness of tax incentives remains debated, highlighting the need for further research to inform evidence-based policymaking and strategic management practices. This study contributes to theoretical understanding by elucidating the complex interplay between taxation policies, consumer behavior, firm strategies, and market outcomes.